Practical Approach to Open Source Intelligence (OSINT) : Volume 2. - Bhardwaj, Akashdeep; ProQuest (firma) (Milton : Taylor & Francis Group, 2025)
This book offers a practical and in-depth exploration of Open-Source Intelligence (OSINT) tailored for cybersecurity professionals, digital investigators, and threat analysts.
Compliance certification by (name): Benetech
Latest accessibility assessment date: 20251113
Compliance certification by (URL): https://bornaccessible.org/certification/gca-credential
Publisher contact for further accessibility information: ebookqueries@tandf.co.uk
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2026. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books